Pengaruh Kualitas Pelayanan Dan Lokasi Terhadap Kepuasan Pengunjung (Studi Kasus Pada Kampung Warna – Warni Jodipan Kota Malang) - Adytia, Lutfi Wahyu; Wahono, Budi; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Kampung Warna-Warni Jodipan is an increasingly popular tourist destination in Malang City. This study aims to analyze the effect of service quality and location on visitor satisfaction in Kampung Warna-Warni Jodipan. Service quality includes friendliness, speed, accuracy, consistency, reliability, and responsiveness of officers in serving visitors. Meanwhile, location factors include ease of access, availability of supporting facilities, comfortable and safe environment, strategic location, and visibility and availability of information.This study used a survey method by distributing questionnaires to visitors of Kampung Warna-Warni Jodipan. The collected data were analyzed using multiple linear regression analysis to determine the effect of service quality and location on visitor satisfaction simultaneously and partially.The results showed that service quality and location have a positive and significant effect on visitor satisfaction in Kampung Warna-Warni Jodipan, both simultaneously and partially. Thus, efforts to improve service quality and strategic location selection are very important to increase visitor satisfaction, which in turn will support the development of tourism in Malang City in a sustainable manner. Keywords: Service Quality, Location, Visitor Satisfaction, Kampung Warna-Warni Jodipan, Tourism.